The Dynamics of Reopening Elementary Schools in Bekasi during Pandemic Covid-19 - Kurniawati Hasjanah; Melissa Balqis; Nana Nurwaesari (SOSIOEDUKASI, 2021)
This paper discusses how the negotiation process between schools, the Bekasi City Government and The Central Government in responding to reopening school in pandemic Covid-19. The Bekasi City Government allow 110 schools to reopening and face to face learning based on their negotiation. Data collection methods are through primary and secondary data collection in the form of interview, news analysis, books and related journals. Some efforts were taken by the Bekasi City Government to reopening schools since August 2020, but unfortunately at that time, reopening schools policy not allowed yet. In the process, The Bekasi City Government used more direct lobbying and negotiation process, which in turn led to The Bekasi City Government's beneficial results to reopening schools on March 2021.